Polarised logics of pedagogy : crises, contexts and classrooms in the Global South - Schweisfurth, Michele, 1962- (Routledge, 2025)
"This novel book demonstrates the polarised logics that exist between exploring cultural, structural, political and historical contexts as a primary focus for pedagogical research versus an interventionist agenda that isolates pedagogy and its components from their environments. Combining theoretical discussions with empirical evidence and case studies, the book provides a synthesising approach to both research and educational planning, recognising pedagogy as an open system while acknowledging that not all teaching methods are equal when it comes to enhancing learning. Considering the so-called 'learning crisis' and 'learning poverty' in the context of Sustainable Development Goal 4 in the wake of the COVID-19 pandemic, this book is also sensitive to concerns about the mental health and wellbeing of young people and the sustainability of the planet. Ultimately providing a timely, informed and balanced discussion of these issues, this book will appeal to researchers, scholars, and post-graduate and doctoral students working in pedagogical research or international and comparative education, and anyone interested in the relationship between education and international development"-- Provided by publisher.
Keywords: Sustainable Development Goals (Project); Comparative education -- Cross-cultural studies.; Teaching -- Developing countries.; Education and state -- Developing countries -- Case studies.; elektronické knihy; electronic books